ACCEPTABLE INDOOR ENVIRONMENTAL QUALITY AT REDUCED ENERGY CONSUMPTION FOR SUSTAINABLE SCHOOLS IN HOT CLIMATE - kattlo, Ahmed (King Fahd University of Petroleum and Minerals (KFUPM), 2016)
Buildings are designed with the aim of providing a comfortable living environment for the occupants. The comfort factors include thermal, visual and acoustical comfort as well as the indoor air quality. The indoor environment quality (IEQ) refers to the performance of a building in delivering an indoor environment to its occupants that meet the expectations of maintaining the occupants' health, comfort, and productivity. Schools have an important function that necessitates careful design and operation to achieve a good learning environment that enhances students’ performance. In order to achieve this, and to reduce absenteeism due to building sickness, schools have to be maintained at the acceptable indoor environment quality. Maintaining a school's functions and operating at acceptable conditions may requires a considerable amount of energy if not properly designed. This research aims at formulating guidelines for sustainable school design and operation by achieving acceptable indoor environmental quality at reduced energy consumption rates. In order to achieve this, a typical school was modeled as the base case. Assessment of the design operational strategies that contribute to sustainability by reducing energy consumption and maintaining acceptable IEQ was done. Typical school buildings in Al-Dammam, Al-Dhahran and Al-Khobar were evaluated for IEQ taking into consideration the energy performance by taking advantage of different opportunities for reducing energy consumption. This was achieved by using the energy simulation program Design-Builder. Optimization for window to wall ratio (WWR), glazing type, air infiltration, and roof and wall thermal insulation was carried out, followed by investigating the impact of lighting type and HVAC systems on the energy consumption and discomfort hours. After conducting optimization for the WWR, glazing type, roof and wall insulation the cooling energy consumption was reduced by 8.7% and the discomfort hours reduced to 213 hours. After upgrading lighting from fluorescent to LED, the reduction in the cooling energy reached 16.5%. While using the DX-Packaged system with optimum parameters reduced the energy consumption by 41% and reduced the discomfort hours to 129hours.
صممت المابني بهدف توفير بيئة معيشية مريحة ومناسبة للسكان. وتشمل عوامل الراحة الحرارية والبصرية والصوتية بالاضافة الى نوعية الهواء الداخلي. نوعية البيئة الداخلية هي مؤشر لاداء المبنى في توفير بيئة داخلية مناسبة للسكان والتي تلبي الحاجات الاساسة من الحفاظ على الصحة والراحة والانتاجية للمستخدمين. تعتبر المداس من المباني ذات الوظائف الهامة التي تستوجب تصميم دقيق وعملي لتتحقيق بيئة تعليمية مناسبة لتعزيز ونطوير اداء الطلاب. من اجل تحقيق ذلك والحد من الغياب بسبب المرض يجب أن يتم الحفاظ على جودة البيئة الداخلية في المدارس. المحافظة على البيئة الداخلية للمدارس قد يتطلب قدرا كبيرا من الطاقة اذا لم تكن مصممة بشكل صحيح. يهدف هذا البحث إلى وضع مبادئ توجيهية لتصميم المدارس المستدامة للحصول على البيئة الداخلية مناسبة مع الاخذ في الاعتبارخفض معدلات استهلاك الطاقة. من أجل تحقيق هذا الهدف، تم نمذجة مدرسة لتمثل نموذج للدراسة والبحث . تم اجراء تقييم لاستراتيجيات تصميم مكونات البنى التي تساهم في الاستدامة عن طريق خفض استهلاك الطاقة والحفاظ على بيئة داخلية مقبولة ومناسبة. تم تقييم مجموعة من المباني المدرسية في الدمام، الظهران و الخبر من ناحية البيئة الداخلية مع الأخذ بعين الاعتبار استهلاك الطاقة للاستفادة من الفرص المختلفة للحد من استهلاك الطاقة. وقد تحقق ذلك عن طريق استخدام برنامج محاكاة الطاقة للمباني. تم اجراء تحليل باستخدام برنامج المحاكاة لاختيار افضل نسبة نوافذ إلى الجداران، نوع الزجاج، تسلل الهواء، العزل الحراري للجدران والسقف . يلي ذلك دراسة تأثير نوع أنظمة الإضاءة والتكييف على استهلاك الطاقة ومستوى الراحة للبيئة الداخلية. بعد إجراء التحليل لنسبة الزجاج للمباني،ونوع الزجاج ،واستخدام العازل للسقف والجدار تم تخفيض استهلاك الطاقة المستخدمة في التبريد بنسبة 8.7٪ وساعات عدم الراحة إلى 213 ساعة. وبعد تغيير الإضاءة من الفلورسنت لاضاء الصمام الثنائي انخفضت الطاقة بمقدار 16.5٪. وبعد تغيير نظام التكييف تم تخفيض استهلاك الطاقة بنسبة 41٪ وتخفيض ساعات عدم الراحة الى 129ساعة
Keywords: Sustainable ArchitectureGreen BuildingGreen ArchitectureArchitectureSustainable ConstructionSustainabilityEnergy SavingLandscape ArchitectureRevit ArchitecturePreservationEnergy ConservationArchitectural DesignSustainable DesignArchitectural Design Using Computer SkillsEnvironmental DesignSustainable BuildingModern ArchitectureEnergy ModelingArchitectural Drawings